RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA PIKOHIDRO (PLTPH) DENGAN TURBIN ULIR (ARCHIMEDES SCREW) - Nurul Irfan AlFandy; Erni Yudaningtyas; Gaguk Asmungi (Jurnal Mahasiswa TEUB, 2022)
ABSTRACT Screw turbine (Archemedes Screw) is a turbine that utilizes the head and water flow per second flowing in the irrigation channel. This water flow will move the turbine screw. The turbine screw movement will rotate the connecting shaft between the turbine and the generator (producing mechanical energy). The shaft will drive the generator so that the mechanical energy from the shaft will be converted into electricity in the generator. This turbine operates at low speed and is newly developed in Indonesia. But as a new turbine technology, until now there are still very few theories or references available regarding the design of screw turbines. The main components of this power generator are the turbine, speed booster (gear and pulley), Boost DC Converter and battery. In measuring water discharge, the floating method is used to calculate the available water discharge. The electric power generated will be stored in a 12v 7.5 Ah battery. The generator power of the device is designed to reach a maximum point, when the water discharge is 134 liters per second, with a voltage of 5 volts which will be increased the voltage to 12.5 volts and a current of 0.53 Ampere as the battery power supply. Keywords : screw turbine, screw angle, renewable energy, new technology, PLTPH, low head